Cent jours dans la vie des campivallensiennes. La grève de 1946 à Salaberry-de-Valleyfield - Bettez, Lucie (Labour / Le Travail, 2008)
Abstract The historiography of Quebec is replete with studies on the working-class movement and its repercussions on labour legislation and the like. However, very few researchers have studied the domestic consequences of a lack of revenue for female workers as well as for the wives and mothers of strikers. This essay looks at these women’s contributions during the 1946 strike at the Montreal Cottons Company in Salaberry-de-Valleyfield, and attempts to analyze the circumstances surrounding the considerable support of the women during this conflict.